A note on the moments of the Riesz–Nágy–Takács distribution - Baek, In-Soo (Journal of mathematical analysis and applications, 2008)
The Riesz–Nágy–Takács (RNT) distribution generalizes the dyadic Riesz–Nágy distribution that has been the subject of recent investigations. In order to study orthogonal polynomials with respect to the RNT distribution it is crucial to know the moments of the distribution. We develop a recurrence relation for these moments.